MITF interacts with the SWI/SNF subunit, BRG1, to promote GATA4 expression in cardiac hypertrophy - Mehta, Gaurav (J Mol Cell Cardiol, 2015)
The transcriptional regulation of pathological cardiac hypertrophy involves the interplay of transcription factors and chromatin remodeling enzymes. The Microphthalmia-associated transcription factor (MITF) is highly expressed in cardiomyocytes and is required for cardiac hypertrophy. However, the transcriptional mechanisms by which MITF promotes cardiac hypertrophy have not been elucidated. In this study, we tested the hypothesis that MITF promotes cardiac hypertrophy by activating transcription of pro-hypertrophy genes through interactions with the SWI/SNF chromatin remodeling complex. In an in vivo model of cardiac hypertrophy, expression of MITF and the BRG1 subunit of the SWI/SNF complex increased coordinately in response to pressure overload. Expression of MITF and BRG1 also increased in vitro when cardiomyocytes were stimulated with angiotensin II or a β-adrenergic agonist. Both MITF and BRG1 were required to increase cardiomyocyte size and activate expression of hypertrophy markers in response to β-adrenergic stimulation. We detected physical interactions between MITF and BRG1 in cardiomyocytes and found that they cooperate to regulate expression of a pro-hypertrophic transcription factor, GATA4. Our data show that MITF binds to the E box element in the GATA4 promoter and facilitates recruitment of BRG1. This is associated with enhanced expression of the GATA4 gene as evidenced by increased Histone3 lysine4 tri-methylation (H3K4me3) on the GATA4 promoter. Thus, in hypertrophic cardiomyoctes, MITF is a key transcriptional activator of a pro-hypertrophic gene, GATA4, and this regulation is dependent upon the BRG1 component of the SWI/SNF complex.